Encephalomyelopathy in a child with acute lymphoblastic leukemia who had received radiotherapy and intrathecal chemotherapy (Bangladesh Journal of Medical Science, 2010)
Encephalomyelopathy is a rare complication of chemotherapy and radiotherapy , and it is a serious cause of morbidity and mortality in the children with Acute Lymphoblastic Leukemia (ALL).A fifteen years old girl, who was diagnosed with ALL 3 years ago, developed CNS relapse 2 years after diagnosis and undertook CNS relapse protocol ( 2400 cGy cranial + 1500 cGy spinal radiotherapy, meanwhile intrathecal chemotherapy with MTX + ARA-C + Prednisone 5 times). Eight months later from radiotherapy, firstly right hemiparesy consequently quadriplegia and quadriparestesia developed, stool and urine incontinence occured, respiration problems started and progressively increased, so she exitus due to respiration deficiency. Key Words: Leukemia; Encephalopmyelopathy; Radiation Myelitis.DOI: 10.3329/bjms.v9i3.6481Bangladesh Journal of Medical Science Vol.09 No.3 July 2010, pp.174-176